Differences between the cooperative learning and the practice style in Rural School. Comparison of two studies of case in a didactic unit of acrosport in the second cycle of primary - José Juan Barba Martín (FEADEF, 2010)
Through these lines it is presented a qualitative investigation in a rural school according to the Physical Education subject. The aim of this investigation is to check if there are any meaningful differences in the teaching of acrosport in accordance with the methodology used: cooperative learning and task assignment. To that effect, different instruments have been used in order to tally the information, which is: a ranking to see the social relationships among students, a practical exam, a pupil's term evaluation sheet, a motivational question paper and a teacher's notebook. Among the results, it could be observed an improvement in the social relationships ranking, in the creative learning and in the perception of the participation of cooperative learning groups. There are some individual facts in these groups where the acceptance from partners and the sense of acceptance from the learner improve with the cooperative learning. These results are similar to other studies which are longer.